2008
DOI: 10.1002/glia.20731
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of human mesenchymal stem cells on dopaminergic neurons through anti‐inflammatory action

Abstract: Parkinson's disease (PD) is a common, progressive neurodegenerative disorder caused by the loss of dopaminergic neurons in the substantia nigra (SN). Numerous studies have provided evidence suggesting that neuroinflammation plays an important role in the pathogenesis of PD. In this study, we used lipopolysaccharide (LPS)-induced in vitro and in vivo inflammation models to investigate whether human mesenchymal stem cells (hMSCs) have a protective effect on the dopaminergic system through anti-inflammatory mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
172
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(176 citation statements)
references
References 47 publications
3
172
0
1
Order By: Relevance
“…Recently, Zhou et al [48] demonstrated that MSC are able to inhibit LPS-stimulated microglia activation and the production of inflammatory factors through diffusible molecules and, within an inflammatory environment, can significantly increase the production of neurotrophic factors, possibly involved in tissue repair. In addition, MSC exert neuroprotective effects on dopaminergic neurons via an antiinflammatory mechanism mediated by the modulation of microglia activation [49]. More importantly, a recent study demonstrated that MSC alternatively activate microglia, thus enhancing its migratory features and ability of eliminating amyloid b [50].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zhou et al [48] demonstrated that MSC are able to inhibit LPS-stimulated microglia activation and the production of inflammatory factors through diffusible molecules and, within an inflammatory environment, can significantly increase the production of neurotrophic factors, possibly involved in tissue repair. In addition, MSC exert neuroprotective effects on dopaminergic neurons via an antiinflammatory mechanism mediated by the modulation of microglia activation [49]. More importantly, a recent study demonstrated that MSC alternatively activate microglia, thus enhancing its migratory features and ability of eliminating amyloid b [50].…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that another positive effect of MSCs therapy lies in its capacity to down-regulate microglia activity (Kim et al 2009, Yan et al 2013). Our results show that SCI clearly causes increase in the number of microglia cells and change in their morphology.…”
Section: Reaction Of Microgliamentioning
confidence: 99%
“…Indeed, hMSCs, that migrate toward lesions (Hellmann et al, 2006;Sadan et al, 2009;Delcroix et al, 2011) may induce a protective or restorative effect on the remaining neurons within the host brain, due to the secretion of a large panel of neurotrophic factors, including brain-derived neurotrophic factor (BDNF) and glial cell line-derived neurotrophic factor (GDNF), which may also enhance endogenous neurogenesis (Levy et al, 2008;McCoy et al, 2008;Bahat-Stroomza et al, 2009;Sadan et al, 2009). MSCs may also modulate the host response to the lesion (Kim et al, 2008) and probably ultimately replace functional cells within the host brain as a few MSCs with neuronal-like morphology and markers were observed in a total lesion model (Levy et al, 2008). We are therefore starting to better understand the mechanisms of action of these cells in the context of PD, while other teams try, with interesting results, to find new ways to deliver the cells to the brain.…”
Section: Adult Cell Therapymentioning
confidence: 99%